Computational simulation of short-range order structures in high-entropy alloys: a review on formation patterns, multiscale characterization, and performance modulation mechanisms - Hongyang Liu; Bo Chen; Rong Chen; Jingzhi He; Dongdong Kang; Jiayu Dai (Advances in Physics: X, 2025)
Short-range order (SRO) structures in high-entropy alloys (HEAs) have recently emerged as a research hotspot in materials science. Conventional perspectives viewed HEAs as chemically disordered systems stabilized primarily by high configurational entropy to maintain single-phase solid solutions. However, growing experimental and computational evidence has revealed the widespread existence of nanoscale SRO structures in HEAs, where such localized ordering significantly impacts mechanical properties and thermodynamic stability. This review systematically summarizes recent advances in understanding SRO structures in HEAs, with a focus on computational simulation methods, including density functional theory (DFT), molecular dynamics (MD), Monte Carlo (MC), and emerging machine learning interatomic potentials(MLPs). By comparing ordered structural features across diverse HEA systems, we elucidate the influence of temperature, composition, and defects on SRO formation dynamics. Furthermore, we explore the origins of SRO, emphasizing thermodynamics, electronic interactions, mechanical load and magnetism effects. A detailed analysis is provided on how SRO modulates alloy performance, particularly its role in regulating stacking fault energy, dislocation behavior, phase transformations. Finally, the prospects for future research directions are discussed.